Should you meet the parents? The impact of information on non-test score attributes on school choice - Elisa Facchetti; Lorenzo Neri; Marco Ovidi (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2021)
We study whether parents value non-test score attributes when choosing school. We exploit an intervention designed to provide hard-to-find information about school environment and day-to-day life at local public-sector institutions. School choice in London provides a unique setting where information on academic performance is already diffused and not shifted by the programme we study. Difference-in-differences estimates show the treatment increased enrolment in state-funded schools with respect to private institutions. We uniquely document that the information particularly affected choices of students with high socio-economic status. In addition, the programme has spillover effects on school choice of unexposed parents. Survey data and text analysis of meeting minutes support the interpretation of our results as effects of information on hard-to-find non-test score school attributes. Our results imply that relatively simple interventions may increase state schools' financial resources and the quality of the student intake.
Keywords: I24; I28; H75; 330; School choice; Non-test score school attributes; Information intervention